Association between the dietary inflammatory index and markers of endothelial and systemic inflammation in hemodialysis patients - Arab, Arman; Karimi, Elham; Nazari, Maryam; Tabibi, Hadi; As’habi, Atefeh (Frontiers in Nutrition, 2023)
Objectives: The current survey aimed to investigate the link between energy-adjusted dietary inflammatory index (E-DII) and risk factors for CVD including markers of endothelial and systemic inflammation in Iranian hemodialysis patients. Methods: Patients on hemodialysis for at least 6 months prior to enrollment were considered eligible in this cross-sectional study. The usual dietary intakes of the hemodialysis individuals were examined through 4 non-consecutive days including 2 dialysis days and 2 non-dialysis days using a 24-h recall approach to calculate E-DII. Multiple linear regression analysis was utilized to investigate the link between E-DII and selected biomarkers of inflammation and oxidative stress including high-sensitive C reactive protein (hs-CRP), serum intercellular adhesion molecule (sICAM), serum vascular cell adhesion molecule (sVCAM), malondialdehyde, and nitric oxide (NO), sE-selectin, and endothelin-1, and beta (β) and 95% confidence interval (CI) was reported. P-value < 0.05 was considered statistically significant. Results: Overall, 291 hemodialysis patients make up our study population. In the crude model, the E-DII score was positively associated with a higher sVCAM-1 (β=177.39; 95% CI: 60.51, 294.26; Ptrend=0.003). Further adjustment for potential confounders attenuated the findings in a way that an increase of 128.72 in the sVCAM-1 was observed when the E-DII score increased from -2.68 to -1.14 (95% CI: 13.50, 243.94). After controlling for potential confounders, E-DII was associated with sE-selectin in HD patients in the highest category of E-DII as compared to the lowest category (β=4.11; 95% CI: 0.22, 8.00; Ptrend=0.039). Conclusion: The present findings suggest that adherence to a pro-inflammatory diet among HD patients is associated with a higher inflammatory status as evidenced by sVCAM-1 and sE-selectin; however, bidirectionality may exist and the role of residual confounders should be taken into account. Therefore, more longitudinal investigations are needed to elucidate the role of diet on the inflammatory status of HD patients.